The time dimension of the links between loss given default and the macroeconomy - Tomáš Konečný; Jakub Seidler; Aelita Belyaeva; Konstantin Belyaev (European Central Bank (ECB), 2017)
Most studies focusing on the determinants of loss given default (LGD) have largely ignored possible lagged effects of the macroeconomy on LGD. We fill this gap by employing a wide set of macroeconomic covariates on a retail portfolio that represents 15% of the Czech consumer credit market over the period 2002-2012. We find an important time dimension to the links between LGD and the aggregate economy in the Czech Republic. The model that allows exclusively for contemporaneous effects includes a number of significant macroeconomic variables, some of which have non-intuitive signs. Nonetheless, a more general time structure of the LGD model makes current macroeconomic variables largely irrelevant and highlights the importance of delayed responses of LGD to the macroeconomic environment.
Keywords: C02; G13; G33; 330; credit losses; loss given default; recovery rates; workout LGD